(untitled) (Italian Journal of Public Health, 2005)
Foodborne diseases still represent an important global public health issue, including Europe and Italy, which endangers the health of the population and leads to socio-economic costs and a threat to the market trend. In developed countries it is estimated that up to one third of the population are affected by microbiological foodborne diseases each year. In these countries, it has been observed that traditional infectious foodborne diseases have decreased while re-emerging and emerging pathogens like Escherichia coli O157, Listeria monocytogenes, Campylobacter jejuni, Norovirus and Hepatitis A virus have increased. In 2004, in Italy the incidence for Listeriosis was 0.06 per 100,000 population and is included among the statutory notifiable diseases. E. coli O157:H7 is not subject to statutory notification in Italy; however, a voluntary national surveillance system for HUS in paediatric patients and for VTEC, has lead to the notification of 429 paediatric HUS cases and 344 clinical cases of VTEC from 1988 to 2004. Data on campylobacteriosis are available thanks to the voluntary notifications received from the Enternet Laboratories: 582 cases were isolated from human clinical specimens in 2004. Furthermore, data from a specific surveillance system for acute viral hepatitis (SEIEVA) shows that the incidence of reported cases in Italy is declining. The necessity to alert the authorities responsible for epidemiological surveillance nationally remains paramount. Communication as well as educational campaigns aimed at different target groups, for example consumers, will play an important role in the prevention of foodborne diseases.